Human Translators and Artificial Intelligence in the Translation of Onomatopoeias and Interjections Based on the Problematic of the Arbitrariness/Motivation of the Sign - Dilber Zeytinkaya (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Sounds that imitate and depict human voices, animal sounds, sounds of nature, and sounds emanating from objects can be defined as onomatopoeia. Interjections are words that convey emotions such as joy, pain, surprise, greeting, approval, disapproval, fear, and hesitation. As an interdisciplinary field of study for linguistics and translation studies, it is important to elucidate how onomatopoeias and interjections are written, how they are translated, and which translation strategies are used. Can an artificial intelligence tool translate onomatopoeias and interjections? In this study, the research object was the French comic strip Lucky Luke–Daisy Town. Published in 1989 byMilliyet Publishing House and in 2000 by Yapı Kredi Publishing House, the Turkish translations of Red Kit–Papatya Kasabası and the English translations of A Lucky Luke Adventure–Daisy Town published in 2016 by Cinebook Publishing House were analyzed. Translations by human translators and translation suggestions of the artificial intelligence tool ChatGPT3.5 were compared and interpreted within the scope of linguistics and translation studies. Because the emergence of onomatopoeias and interjections is associated with the emergence of language, assumptions about the emergence of language are included. Sound symbolism, in onomatopoeia is one of the main subject areas, was emphasized, and the relationship between sound and meaning was analyzed. The concept of language sign was clarified, and the arbitrariness/motivation of the sign was discussed. The study concluded that human translators preferred the substitution strategy the most, used the borrowing strategy and perspective shifting strategies at the same rate, and preferred the word-for-word translation strategy the least. The results revealed that artificial intelligence cannot provide perfect results in every field and under every condition. Thus, human translators cannot be replaced for a long time, particularly in the translation of works containing humor, metathesis, onomatopoeias, and interjections.